Diagnosis of the Incorporation Process (Onboarding) of Personal at ESE Santiago de Tunja - Jaime-Barón, Luis-Edilio; Reyes-Vargas, Lila-Inés; Paredes-Casas, Auly-Fernando (Universidad Pedagógica y Tecnológica de Colombia, 2022)
Presents the results obtained in the diagnosis of the reception and incorporation system of personnel in the Santiago de Tunja E.S.E, a state social enterprise in the department of Boyacá - Colombia. Focusing its development on how the Onboarding strategy would be developed for a first phase, which seeks to diagnose the procedures established in the organization for the incorporation and retention of a new worker. Therefore, as a first step we focus on the conceptualization of the "reception system" or "incorporation of personnel", with emphasis on the theories proposed by different authors, and considering the clear delimitation of the variables or study dimensions that are presented in the information collection instrument built for that purpose. The development of this instrument was carried out considering a documentary review, in which databases such as Scopus and Science Direct were used, among others. Next, the diagnostic results of the reception system or the incorporation of personnel are determined and presented, by applying the instrument built and validated with the Cronbach's Alpha index. The applied methodology is based on quantitative descriptive research, under the field research model, and data processing that includes the use of statistical software SPSS version 26; as part of the results found, it was possible to establish that the collaborators of the E.S.E. feel motivated within the organization and their perception is that the organization interacts appropriately with them.